2002
DOI: 10.1007/bf03020617
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil moisture content from L- and P-band AirSAR data: A case study in Jeju, Korea

Abstract: Abstract-During the PacRim AirSAR campaign in Korea, the ground truth data about soil moisture content and surface roughness characteristics were collected. We intend to retrieve the surface parameters over the bare soil from multipolarization and multi-frequency AirSAR data. In this study, the theoretical scattering model, the IEM model is inverted by two existing algorithms -the multi -dimensional regression technique by Dawson et al.[1] and the inversion using 3-layer artificial neural networks (ANNs) [4]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The BC obtained from microwave depends on the frequency, polarization, incidence angle of radar configuration and surface parameters such as dielectric properties and Geocarto International 845 surface roughness. Kwon et al (2002) showed that the sensitivity of BC depends on the range of frequency, incidence angle, surface roughness and soil moisture content. It explained that BC has different polarizations depending on soil moisture and surface roughness parameters.…”
Section: Microwave Remote Sensing Datamentioning
confidence: 99%
“…The BC obtained from microwave depends on the frequency, polarization, incidence angle of radar configuration and surface parameters such as dielectric properties and Geocarto International 845 surface roughness. Kwon et al (2002) showed that the sensitivity of BC depends on the range of frequency, incidence angle, surface roughness and soil moisture content. It explained that BC has different polarizations depending on soil moisture and surface roughness parameters.…”
Section: Microwave Remote Sensing Datamentioning
confidence: 99%